Medicine and the marketplace : the moral dimensions of managed care - Wong, Kenman L., 1964- (University of Notre Dame Press, 1998)
"'Medicine and the Marketplace' is a comprehensive analysis of the ethical dilemmas raised by managed health care. The emerging dominance of managed care provided by profit-seeking corporations has intensified the public's concern that business goals of maximizing profits will destroy medicine's traditional commitment to patient well-being. Society is left to wonder how physicians can properly honor their duties to patients when the managed care organizations that employ them have financial obligations to shareholders. [This] timely book addresses issues raised by the new intersections of business and medicine with an ethical assessment of emerging health care arrangements. By focusing on organizational ethics, he offers an integrative framework that seeks to balance patient, societal, and corporate interests."--Jacket.